'Bordering' life: denying the right to live before being born. Issue 4 (3rd September 2019) - Tiwari, Meera
ABSTRACT: This study pushes the boundaries of the border thinking discourse to examine grassroots perceptions of foeticide together with how women are valued in a society that is underpinned by preference for a male child. Using a bordering conceptual framework, the paper re-visits the female positionality within epistemic locations of culture and societal values in both colonial and the modern Indian context. Grounded in primary research in the state of Haryana that exhibits lowest female to male ratio at birth in the country, the analyses indicate rigid or at best sluggish movements in social norms as the key driver for India's declining sex ratio. The border thinking discourse further enables to situate the different aspects of female positionality and gender perceptions in the society into the specific domains of the bordering conceptual framework. This offers a novel approach to engage with social norms that border life and opportunities for females in the society.